Nutritional status and metabolic disorders in children 8 to 10 year-old with history of fetal macrosomia, Tacna, Peru - Ticona Rendón, Manuel (2014)
Introduction: Fetal macrosomia is a risk factor for metabolic disorder and obesity in childhood and adulthood. Objectives: To determine nutritional status and metabolic disorders of children with history of fetal macrosomia in Tacna. Design: Prospective, descriptive and longitudinal study. Institution: Hipolito Unanue Hospital, Tacna, Peru. Patients: Fifty children 8 to 10 year-old born at Hipolito Unanue Hospital of Tacna, with history of birth weight over 4 500 grams were studied. Children with chronic diseases predisposing to overweight or obesity were excluded. Interventions: The nutritional status was assessed by current body mass index (BMI) according to age using World Health Organization charts; blood pressure was measured in millimeters of mercury and fasting serum sample was obtained for enzymatic methods analysis to assess glucose, triglycerides, total cholesterol, HDL cholesterol and LDL cholesterol. Main outcome measures: Nutritional status and metabolic disorders. Results: At 8 to 10 years old 86% (43/50) of children with fetal macrosomia were overweight (30%) or obese (56%). Significant association between nutritional status of children with fetal macrosomia and sex was noted; boys were significantly more overweight and obese than girls (p = 0.014). Frequency of diabetes mellitus, hypercholesterolemia, abnormal HDL cholesterol, elevated LDL cholesterol, hypertryglycerydemia, and diastolic arterial prehypertension was respectively 6%, 8%, 30%, 14%, 46% and 10%. Conclusions: Children 8 to10 years old with history of fetal macrosomia had high frequency of obesity and metabolic disorders.